2019
DOI: 10.2196/12121
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Mental Health Delivery Through Behavioral Economics and Implementation Science: Protocol for Three Exploratory Projects

Abstract: Background Efficacious psychiatric treatments are not consistently deployed in community practice, and clinical outcomes are attenuated compared with those achieved in clinical trials. A major focus for mental health services research is to develop effective and cost-effective strategies that increase the use of evidence-based assessment, prevention, and treatment approaches in community settings. Objective The goal of this program of research is to apply insights from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 120 publications
0
20
0
Order By: Relevance
“…PSD is well-established as an approach to development of new technologies and therefore may be more naturally incorporated into app development 7 , 8 . Behavioral economics has traditionally focused on economic decision-making 51 , then was applied to behavioral health 52 but has only more recently been used in the context of mental health interventions 53 . The results of our meta-analysis suggest that increasing the number of engagement techniques may be beneficial, and so it is likely that designers may need to draw from a range of engagement approaches to maximize the impact of app-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…PSD is well-established as an approach to development of new technologies and therefore may be more naturally incorporated into app development 7 , 8 . Behavioral economics has traditionally focused on economic decision-making 51 , then was applied to behavioral health 52 but has only more recently been used in the context of mental health interventions 53 . The results of our meta-analysis suggest that increasing the number of engagement techniques may be beneficial, and so it is likely that designers may need to draw from a range of engagement approaches to maximize the impact of app-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that discrete choice experiments can be used as a stakeholder engagement strategy to identify attributes of EBIs and implementation strategies that can make the adoption of an EBI more attractive [ 64 66 ]. For example, it can be used to select and tailor implementation strategies to the needs of providers [ 67 ] or to barriers and facilitators [ 58 ] and to evaluate the appropriateness of these strategies [ 68 ]. Its advantages over traditional surveys include a more granular understanding of people’s decisions based on how they value options [ 67 ] and a better reflection of the trade-offs often involved in decisions related to implementation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 There is a growing list of completed and planned studies in this area for interested readers. [48][49][50][51][52][53][54][55][56][57] Cost-effectiveness analyses have common approaches for presenting results. 58 There is growing literature on how to best present information on the budget impact for implementation science.…”
Section: Discussionmentioning
confidence: 99%